The Effect of Trust Towards Online Repurchase Intention With Perceived Usefulness As An Intervening Variable: A Study on KASKUS Marketplace Customers - Setyorini, Retno; Nugraha, Rizky Prima (School of Business and Management Institut Teknologi Bandung, 2016)
Abstract. Using the internet, producers and consumers can get more practical alternative to sell or to buy products or services that they want. Internet adoption is very important to the success of a company. The purpose of this study is to know the effect of trust towards online repurchase intention with perceived usefulness as an intervening variable. The respondents in this study consist of 400 KASKUS customers in Indonesia who has made twice or more transactions. The sampling method used in this study is convenience sampling. This research included in descriptive research with causal approach. Techniques of data analysis in this study using descriptive analysis and path analysis to determine the effect of each variable directly and indirectly. Therefore, the paper discusses the outcomes from The Effect of Trust Towards Online Repurchase Intention With Perceived Usefulness. The study show that trust has percentage of 74.656%, perceived usefulness 78.975% and online repurchase intention 78.479%. Itâ€™s mean that trust, perceived usefulness and online customers repurchase intention KASKUS customers included in good category. Â Keywords: Indonesia, Marketplace, Online Repurchase Intention, Perceived Usefulness, Trust